Blur detection in fundus images - Chernomorets, Alexandra A.; Krylov, Andrey S. (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
The paper addresses the problem of retinal image quality assessment, in particular the problem of blur detection for retinal images is considered. The blur value is obtained using an analysis of blood vessel edge widths as the vasculature is the object that is least prone to structural distortion even if blurred. The paper presents the model of a general edge based on the Gaussian filtering and also the paper presents the algorithm for edge width estimation. The values of the parameters for the algorithm are chosen according to experiments on synthetic data.